ERS International Congress 2021: highlights from the Pulmonary Vascular Diseases Assembly. Issue 2 (23rd May 2022) - Lichtblau, Mona; Piccari, Lucilla; Ramjug, Sheila; Bokan, Aleksandar; Lechartier, Benoit; Jutant, Etienne-Marie; Barata, Margarida; Garcia, Agustin Roberto; Howard, Luke S.; Adir, Yochai; Delcroix, Marion; Jara-Palomares, Luis; et al.
This article aims to summarise the latest research presented at the virtual 2021 European Respiratory Society (ERS) International Congress in the field of pulmonary vascular disease. In light of the current guidelines and proceedings, knowledge gaps are addressed and the newest findings of the various forms of pulmonary hypertension as well as key points on pulmonary embolism are discussed. Despite the comprehensive coverage of the guidelines for pulmonary embolism at previous conferences, discussions about controversies in the diagnosis and treatment of this condition in specific cases were debated and are addressed in the first section of this article. We then report on an interesting pro–con debate about the current classification of pulmonary hypertension. We further report on presentations on Group 3 pulmonary hypertension, with research exploring pathogenesis, phenotyping, diagnosis and treatment; important contributions on the diagnosis of post-capillary pulmonary hypertension are also included. Finally, we summarise the latest evidence presented on pulmonary vascular disease and COVID-19 and a statement on the new imaging guidelines for pulmonary vascular disease from the Fleischner Society. This article summarises communications from #ERSCongress 2021 on pulmonary embolism diagnosis and treatment, PAH and CTEPH during the COVID-19 pandemic and beyond, novelties in post-capillary PH and in PH associated with respiratory diseases https://bit.ly/3ASDO21